PARTISIPASI DALAM PENGAMBILAN KEPUTUSAN STRATEGIS DI PONDOK PESANTREN - Syuhud, Syuhud (JURNAL AL-TANZIM, 2019)
Decision making is one of the leader's strategic tasks in carrying out his leadership duties. Therefore information, participation from various parties and aspects in the management system, will determine the quality of decisions made by the leadership. Kyai as the highest leader of pesantren will determine the direction of development and make quality long-term strategic decisions in the face of global change. The ability of Kyai in managing information from subordinates in society can be seen from his decision making methods, namely full power and power sharing. The focus of this research lies in how Kyai utilize and manage information to make a positive contribution to produce quality decisions in Pondok pesantren Kyai Syarifuddin, Lumajang ? This research uses a qualitative approach with case study. The results showed that Kyai as a leader in pesantren have full authority in decision making, both short and long term. However, However, the Kyai as leaders of pesantren still ask for input information from the pesantren administrators as a material consideration in making quality decisions. The quality of decisions determined by a leader is very dependent on the extent to which information material data considerations provide an influence on the outcome of the decision.